Screening Criteria for Colorectal Cancer for Patients with Type II Diabetes Mellitus - Alexandra AGACHE; Sabin BOTEA; Petronel MUSTATEA; Florin BOBIRCA; Traian PATRASCU (Modern Medicine)
Colorectal cancer and diabetes mellitus represent a major public health issue, first, by the number of new cases which are at an alarming rate. Secondly, by the negative effect over the quality of life, socio-economic status and lifespan, representing high morbidity and mortality causes. Diabetes Mellitus is the disease of the century with a global prevalence (standardised-age) which doubled since 1980, rising from 4.7% to 8.5% in adult population. In 2012, the estimated number of fatalities caused by diabetes mellitus and other related complications were at 3.7 million, out of which 43% were patients under the age of 70. Neoplasia represents the second cause of death, after cardiovascular disease. Colorectal cancer (CRC) ranks the 3rd regarding the global neoplasia incidence (10.2%) and the second regarding the mortality (9.5% of all cancer deaths). Colorectal cancer screening refers to the periodic evaluation of asymptomatic patients at risk of developing this neoplasia. Colorectal cancer has a number of peculiarities that make it ideal for screening. Since the end of the 19th century, the suspicion has been raised that diabetes mellitus has been involved, through directly etiological mechanisms, in carcinogenesis (breast, endometrium, colorectal, pancreas, liver, non-Hodgkin lymphoma). At the moment, there is already a consensus in the literature on the role of diabetes as an independent risk factor for colorectal cancer. However, despite the existence of numerous experimental evidence, epidemiological studies and meta-analyses, there is currently no adaptation of colorectal cancer screening for these patients. Material and method: Prospective case-control study conducted over a 2-year period including a number of 442 patients presented at „Dr. I Cantacuzino” Clinical Hospital, asymptomatic, who underwent lower digestive endoscopies in order to assess and define using anamnestic, clinical and paraclinical criteria, the profile of the patient with type II diabetes mellitus that should be given an endoscopic examination because diagnosing precursor lesions or even CRC is likely probable. Results: In the analyzed group, statistically significant correlations (p<0.05) were recorded between positive colonoscopy results (defined as precursor lesions - polyps - or tumors) and certain clinical characteristics (age, sex, BMI, duration of diabetes, type of antidiabetic treatment) and also paraclinical (reactive C protein and glycated hemoglobin). Conclusions: Criteria of patients with type II diabetes who have the maximum probability of developing colorectal cancer have been outlined. Thus this patient is more likely male, with a BMI > 25, aged over 60 years, with an unbalanced diabetes mellitus counted by HbA1c > 7 mg/dL, with over 5 years of diabetes evolution, in treatment with insulin most likely or combined insulin with oral antidiabetics and with an inflammatory biological profile expressed by PCR> 2 mg/dL threshold values.